Neonatal complications and referral practices at birth: insights from a population-based study in the Indian state of Bihar - Rakhi Dandona; G Anil Kumar; Tanmay Mahapatra; Md Akbar; Moutushi Majumder; S Siva Prasad Dora; Indu Bisht (BMJ Open)
Objectives To explore neonatal survival by type of neonatal complications at birth and referral pattern for these complications by place of delivery.Setting Bihar, India.Participants Women aged 15–49 years who had given live birth between July 2020 and June 2021.Primary and secondary measures Prevalence of neonatal complications at birth, referral pattern by complication and neonatal deaths by type of complication.Results Data were available for 6767 (81.8%) newborns including 717 neonatal deaths. The prevalence of at least one neonatal complication at birth was reported for 32.9% (95% CI 32.4 to 33.4) newborns, with the most common complications including difficulty in breathing (21.9%), high fever (20.7%), low birth weight (12.5%) and jaundice (13.2%). A total of 578 (26.6%; 95% CI 25.8 to 27.4) neonates with complications at birth were referred to another health provider, predominantly to private sector (68.1%, 93% and 78.7% from public facility, private facility and home). The complications with high referrals included meconium aspiration syndrome (64.1%; 95% CI: 61.1 to 67.1), inability to pass urine (54.7%; 95% CI: 42.1 to 67.2), difficulty in suckling (49.7%; 95% CI: 46.9 to 52.5), cold to touch (48.5%; 95% CI: 43.5 to 53.6), inability to cry (47.2%; 95% CI: 44.2 to 50.1), pneumonia (45.6%; 95% CI: 42.0 to 49.1), difficulty in breathing (44.0%; 95% CI: 42.5 to 45.6) and lethargy (43.5%; 95% CI: 38.4 to 48.6). Referrals were linked to higher neonatal deaths, in particular, among neonates born at home and referred for complications (84.7%; p<0.001) compared with those born in public facilities (59.8%) or private facilities (47.3%) and referred for complications.Conclusions With one-third of the neonates reported to have complications at birth and those referred more likely to die, critical gaps in addressing neonatal complications at birth and improvement in the referral services are urgently needed to reduce neonatal mortality.